Comparative Analysis of Student’s Academic Performance in Online and Face to Face Teaching of Biochemistry at HITEC-IMS Taxila - Ambreen Javed, Raheela Yasmin, Ummara Aslam, Manal Rauf, Sana Umar, Ayesha Javed, Shahid Rauf, Sumaira Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: During Covid pandemic the teaching/learning shifted from face to face to online. All institutions around the world developed learning environment for the students to facilitate distant learning. Subsequently assessments also followed online. After opening of the institutions on campus learning and assessments were carried out as usual. Objective: To see the effectiveness of teaching methods (online versus on campus) and to suggest improvement in both methods of teaching. Study Design: Retrospective comparative study Place and Duration of Study: Hitec-IMS, Taxila Pakistan from 1st September 2021 to 29th February 2022. Methodology: One hundred and ninety six academic performances of students in both the methods of learning were enrolled. Using purposive sampling technique, the EOB results of online and on campus were analyzed. Results: The better performance of student in term of summative assessments during online learning. Conclusion: Students found online environment better for learning and performing during examinations. Keywords: HITEC-IMS (Hitec Institute of Medical Sciences), NUMS (National University of Medical Sciences), EOB (end of block)